Application of black soldier fly larvae in decentralized treatment of faecal sludge from pit latrines in informal settlements in Kampala city - Tokwaro, Richard; Semiyaga, Swaib; Niwagaba, Charles B.; Nakagiri, Anne; Sempewo, Jotham Ivan; Muoghalu, Chimdi C.; Manga, Musa (Frontiers in Environmental Science, 2023)
Faecal sludge management (FSM) in urban areas of low-and middle-income countries (LMICs) is not properly implemented due to inaccessibility of sanitation facilities and high faecal sludge (FS) emptying costs, among others. Unlike in solid wastes and fresh human excreta, use of black soldier fly larvae (BSFL) in treatment of FS from pit latrines has not yet been explored, which are the most common sanitation facilities in urban areas of LMICs. Additionally, the optimal conditions for efficient FS degradation, such as moisture content, feeding rate and larval density are not yet well known. Against this backdrop, the overarching aim of this study was to determine the effectiveness of BSFL in treating FS under different conditions of moisture content, feeding rate and larval density. Also, the quality of residue left after treatment was assessed. FS samples were collected from lined and unlined pit latrines in Bwaise I parish in Kampala, Uganda and experiments were set up to feed 10-day old larvae. The optimum feeding rate, larval density and moisture content were found to be 50 mg/larvae/day, 200 larvae (1.33 larvae/cm2) and 60%, respectively. The reduction efficiency at optimum conditions were 69% and 63% for FS from lined and unlined pit latrines, respectively. It was further noted that BSFL can feed on FS from pit latrines without dewatering it, hence no need of dedicated step or unit for dewatering. The properties of the residue left after treatment were within the allowable limit for use as compost except for helminth eggs concentrations. Therefore, in urban informal settlements, BSFL can be applied for effective treatment of FS from pit latrines while generating good quality residue, which provides an additional value chain in FSM.